MEKANISME CORPORATE GOVERNANCE DAN KUALITAS LABA - Novita Indrawati; Lilla Yulianti (PEKBIS, 2012)
This research tried to examine the influence of corporate governancemechanism, namely institutional ownership, managerial ownership, composition ofboard of commissioner and audit committee to earning quality. This research takessample from 40 companies in the manufacturing sector at the Indonesian StockExchange, which were published in financial report in the year 2006. The method ofanalysis of this research used mulyple linear regression.The result showed that onlyinstitusional ownership variable significant effect on earning quality. It indicates thatinstitusional ownership can be monitoring the activity management because thisinvestor is sophisticated investor and informed investor about companies, howevermanipulate earning caused by asymetric information can increased. Than, variablesmanagerial ownership, composition of board of commisioner, and audit committeenot significant effect on earning quality.